Inside view : a leader's observations on leadership - Ulmer, Walter F. (Report (Center for Creative Leadership) ;, 1997)
With thirty-seven years in the U.S. Army, retiring as a three-star general, and nine years as the president and CEO of the Center for Creative Leadership, Walter F. Ulmer, Jr., has a wealth of leadership experience. He is also an exceptionally thoughtful person committed to learning from his experience. This book, selected from columns that he wrote for CCL's periodical Issues & Observations and introduced by an adaptation of an essay written for the Kellogg Leadership Studies Project, demonstrates his understanding of both practice and theory, and reminds us that there can be no true leadership without learning.